2016
DOI: 10.1176/appi.ajp.2016.15091228
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Nutraceuticals for Depression: A Systematic Review and Meta-Analyses

Abstract: Current evidence supports adjunctive use of SAMe, methylfolate, omega-3, and vitamin D with antidepressants to reduce depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(191 citation statements)
references
References 87 publications
4
177
0
10
Order By: Relevance
“…We introduced one at a time to the fully adjusted models of tables 2 and 3 variables representing inflammation (via log(C-reactive protein)), cardiovascular disease risk (via Framingham Global CVD Risk Score), reproductive history (via number of live births), and dietary elements associated with depression. The dietary variables consisted of folate, vitamin B12, zinc, vitamin D (Sarris et al, 2016) and selenium (Conner et al, 2015). Because 21 women who self-reported that they were 0 years postmenopause may actually have been perimenopausal by STRAW+10 criteria (Harlow et al, 2012), we conducted the analyses in Tables 2 and 3 again after excluding these women.…”
Section: Methodsmentioning
confidence: 99%
“…We introduced one at a time to the fully adjusted models of tables 2 and 3 variables representing inflammation (via log(C-reactive protein)), cardiovascular disease risk (via Framingham Global CVD Risk Score), reproductive history (via number of live births), and dietary elements associated with depression. The dietary variables consisted of folate, vitamin B12, zinc, vitamin D (Sarris et al, 2016) and selenium (Conner et al, 2015). Because 21 women who self-reported that they were 0 years postmenopause may actually have been perimenopausal by STRAW+10 criteria (Harlow et al, 2012), we conducted the analyses in Tables 2 and 3 again after excluding these women.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical tests and models of depression showed antidepressant-like activity of zinc [915]. Clinical data pointed towards potential benefits of zinc administration in depressed patients [16, 17]. Zinc supplementation was shown to be effective as an adjunct therapy [6, 7, 18] or as a stand-alone intervention [19, 20] for depression.…”
Section: Zincmentioning
confidence: 99%
“…Importantly, zinc supplementation of therapy involving administration of imipramine was found to be more effective than administration of imipramine plus placebo in treatment-resistant patients [18]. Although a recent systematic review and meta-analysis of adjunctive nutraceuticals for depression found mixed results for zinc [17], zinc supplementation shows promise as a strategy for improving an inadequate response to antidepressants.…”
Section: Serotonin (5-ht)mentioning
confidence: 99%
“…The coadministration of standardized pharmaceutical-grade nutrients, referred to as nutraceuticals, may provide an effective and safe approach to enhancing AD effects, by either synergistically augmenting a particular activity of an AD or providing a range of additional biological effects. 23 All nutraceuticals are generally well tolerated, with gastrointestinal adverse events most commonly reported across all nutraceutical groups. Current evidence supports adjunctive use of S-adenosylmethionine, methylfolate, omega-3, and vitamin D with ADs to reduce depressive symptoms.…”
Section: New Augmentation Strategymentioning
confidence: 99%
“…Current evidence supports adjunctive use of S-adenosylmethionine, methylfolate, omega-3, and vitamin D with ADs to reduce depressive symptoms. 23 However, depression is not simply the result of neurotransmitter abnormalities. A large body of evidence points to a deregulated endocrine and inflammatory response system and reduced neurogenesis, in the pathogenesis of depression.…”
Section: New Augmentation Strategymentioning
confidence: 99%